BIAYA IKLAN DAN PROMOSI SERTA PENGARUHNYA TERHADAP HASIL PENJUALAN PT. INDOFOOD SUKSES MAKMUR TBK. - Lilik Yuliawati (Cakrawala - Jurnal Humaniora, 2019)
Food and beverage industry is a sub-sector of manufacturing industry which contributes the most to GDP where the prices always increase every year.  The food and beverage industry in Indonesia has a monopolistic competition market structure where there are many companies engaged in this field and none of these companies has a market share of more than 10%. However, there are several companies that are quite well-known for their flagship brands that are very much in demand by Indonesian people, one of which is PT. Indofood Sukses Makmur, Tbk. In its business activities, each company requires some costs for advertising and promotion in order to make its products known to the public. However, as a big company that is well-known to the public, does PT. Indofood Sukses Makmur, Tbk still need vigorous advertising and promotion so that its products sold well? This research aims to know the effect of advertising and promotion costs on the sales of PT. Indofood Sukses Makmur, Tbk. The data used is secondary data. This research used descriptive and quantitative methods. The data analysis technique of the research is Simple Linear Regression. The result of this research shows that there is a significant effect of advertising and promotion costs on the sales of PT. Indofood Sukses Makmur, Tbk. In another words, as one of the big companies in food and beverage industry, PT. Indofood Sukses Makmur Tbk still needs advertising and promotion to increase the sales volume.